Animal-assisted intervention: the "Paws for Wellness Program" - Olagunju, Andrew T. (Innovative treatment approaches in forensic and correctional settings, 2024)
Animal-assisted intervention (AAI) involves a “deliberate and meaningful inclusion of animals into human health, wellbeing, or educational interventions.” AAI has been shown to increase patients’ wellbeing through social interaction with certified therapy animals and their handlers during a visit with individual patients or small groups. The Paws for Wellness program is a canine-assisted intervention program (a type of AAI) developed for individuals with various mental health diagnoses and risk profiles in forensic-correctional units to promote emotional wellbeing, foster social interaction, and reduce isolation through touch and connection with the animal during visits. The program allows patients to engage in sensory and touch-based interventions, which are often restricted in secure settings with offenders because of risk and may be deemed inappropriate. Individual patients have the opportunity to hold, pet, walk, feed, play with, and brush a designated dog. The interaction takes place in a safe and monitored environment with optimum mitigation of risk. Through the program, patients develop new leisure skills and engage in social interactions to improve their social, cognitive, physical, and emotional wellbeing. This chapter describes the Paws for Wellness program, focusing on the theoretical underpinnings, implementation, and evaluation, and provides a set of recommendations for adaptation in comparable settings.